Morphological aspects of eyeball functional units during exogenous hypothyroidism, induced by mercazolilum. - Shchur, M. B.; Yashchenko, A. M. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. We have conducted this research taking into account the growth of thyroid gland pathology, as a result – endocrine ophthalmopathy and the lack of literature data about microscopic morphologic changes in functional units of the eyeball during hypothyroidism. Оbjective of the study was to investigate morphological features of rat eyeball structural components during mercazolil-induced experimental hypothyroidism. Methods. The research was conducted on 35 mature Wistar male rats, with weight 180-240 g (10 control and 25 experimental). Exogenous hypothyroidism was induced by daily administration of food with thyreostatic drug mercazolilum (“Здоров’я”, Kharkiv, Ukraine) at a dose of 5 mg / kg body weight within 14 days. The investigated histological material (thyroid glands and eyeballs) was taken after animal euthanasia by an overdose of anesthesia, than fixed in Buen solution, dehydrated, compacted and embedded in paraffin. Sections 5-7 μm thick were stained by hematoxylin and eosin. Function control of thyroid gland was performed by investigation of thyroid gland’s morphology. Results. Investigation of structural components of the eyeball during mercazolilum-induced hypothyroidism, which was accompanied by the change of follicles size, the height of thyrocytes and colloid consistency in the thyroid gland, has shown that there is a local detachment of the superior layer of epithelium, its keratinisation. Change of cells shape and kariopicnosis was observed in the basal layer, hypertrophy of some cells, their cytoplasm hydropic dystrophy and detachment from the basal membrane. In some intermediate layer cells kariopicnosis and dystrophic changes in cytoplasm was observed. In corneal stroma we saw edema, interleaving of collagen fibers, minor lymphocyte infiltration, especially in the dilated venous sinus, local detachment of the anterior chamber endothelium, the corneal epithelium and ciliary body lymphocyte infiltration. In retina we observed edema and degenerative changes of some neurons in the inner nuclear layer, most likely because of the edema, change of retina arterial lumen diameter and thus neuron nutrition. During exogenous hypothyroidism there were also destructive changes in lacrimal gland and its intensive lymphocyte infiltration. At the same time, there was observed a leukocyte infiltration in the conjunctival part of the eyelid and increase of adipose tissue near the orbita bone part. Conclusion. Morphological investigations of the structural components of the eyeball showed negative influence of mercazolilum-induced exogenous hypothyroidism on functional units of rat eyeballs. The major morphologic changes were diagnosed in the cornea, while less – in other functional units.